A Systematic Approach for the Design, Fabrication, and Testing of Microstrip Antennas Using Inkjet Printing Technology. (30th May 2012) - Al-Naiemy, Yahiea; Elwi, Taha A.; Khaleel, Haider R.; Al-Rizzo, Hussain
Abstract : We present a systematic approach for producing microstrip antennas using the state-of-the-art-inkjet printing technique. An initial antenna design based on the conventional square patch geometry is adopted as a benchmark to characterize the entire approach; the procedure then could be generalized to different antenna geometries and feeding techniques. For validation purposes, the antenna is designed and simulated using two different 3D full-wave electromagnetic simulation tools: Ansoft's High Frequency Structure Simulator (HFSS), which is based on the Finite Element Method (FEM), and CST Microwave Studio, which is based on the Finite Integration Technique (FIT). The systematic approach for the fabrication process includes the optimal number of printed layers, curing temperature, and curing time. These essential parameters need to be optimized to achieve the highest electrical conductivity, trace continuity, and structural robustness. The antenna is fabricated using Inkjet Printing Technology (IJPT) utilizing Sliver Nanoparticles (SNPs) conductive ink printed by DMP-2800 Dimatix FujiFilm materials printer.